Impact of COVID-19 lockdown in depression, anxiety and stress among students in polytechnic of Santarem and Leiria. (3rd August 2021) - Silva, Mário; Gonzaga, Luís; Figueiredo, Maria do Carmo; Rosa, Marta; Matos, Rui; Amendoeira, José
Abstract: Background: The context of coronavirus on higher education caused upsetting consequences on students' lives. The restrictions on social mobility and the consequent reduction of interpersonal contacts brought them unprecedented stressful situations. The extent and quality of adaptation to these situations, due to the uniqueness of each person's resources, needs to be early known preventing eventual and serious psychological disorders. This study aimed to assess stress, anxiety, and depression among undergraduate students from both Santarém and Leiria Polytechnic Institutes. Methods: A descriptive cross-sectional correlational study was performed in the period immediately after the first lockdown. Participants were 775 students (females = 73.5%), aged between 17 and 55 years. All of them completed measures of the Depression Anxiety and Stress Scale-21 (DASS-21; in the Portuguese version EADS, by Pais-Ribeiro, Honrado e Leal, 2004). Collected data were analyzed with IBM SPSS Statistics for Windows software, Version 27.0. Results: According to DASS-21 scoring instructions (Lovibond & Lovibond, 1995), results showed that most participants had experienced a normal level of depression (72.5%), anxiety (79.7%) and stress (87.6%). However, about 4.7% and 1.8% of respondents, respectively, report a severe or extremely severe level of anxiety or depression. We also found significant differences for the three dimensions in terms of polytechnic institute attended, gender, age categories, and marital status. Conclusions: The findings suggest that higher education institutions must understand this phenomenon experienced and develop strategies for improving students' mental health, especially in vulnerable groups. The importance of a transdisciplinary approach is emphasized and the involvement of all educational stakeholders is encouraged.